A method for preparing polyaniline film by self-assembly
Through the self-assembly preparation method, the large-area preparation of polyaniline film on any substrate is achieved, and the thickness controllability of the polyaniline film is solved, which solves the problem of low thickness controllability in the prior art, and improves the response speed and performance of the device.
Patent Information
- Application Number
- CN202310349760.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-04
AI Technical Summary
In the prior art, when preparing polyaniline films, the thickness controllability is low, and it is difficult to prepare on any substrate on a large area, affecting the response speed and driving voltage of the device.
The self-assembly preparation method is adopted, and the polyaniline film is self-assembled at the gas-liquid interface to form a film through interfacial recrystallization, and film preparation of different thicknesses is achieved through layer by layer assembly, which is suitable for the transfer of any substrate.
It realizes the large-area preparation and thickness controllability of polyaniline films, is suitable for applications in different fields, and improves the response speed and performance of conductive polymer electrical devices.
Smart Images

Figure CN116396511B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive polymer film preparation, and in particular to a self-assembly preparation method of a polyaniline film with controllable thickness. Background Art
[0002] Conductive polymer electrochromic devices are mainly composed of three parts: working electrode, electrolyte and counter electrode. The electrochromic layer, also known as the working electrode, is the core layer of the entire electrochromic element and the layer where the color change reaction occurs. The electrochromic layer mainly appears in the form of electrochromic film.
[0003] Electrochromic materials can be divided into two categories: organic electrochromic materials and inorganic electrochromic materials. Inorganic electrochromic materials are mainly represented by transition metal oxides such as NiO and WO3. Compared with inorganic electrochromic materials of transition metal oxides, organic electrochromic materials have the advantages of rich colors, light weight, low voltage drive, easy structural design, and relatively fast response speed.
[0004] Among them, conductive polymer organic electrochromic materials have very good application prospects in the fields of flexible display, wearable, and multifunctional electrochromic devices due to their good bending, folding, and stretching properties. Common conductive polymers include polyaniline (PANI), polypyrrole (PPy), polythiophene (PTH), etc. Among them, polyaniline is favored because of its easy availability of raw materials, simple synthesis, high conductivity, potential solution, melt processing possibilities, and good environmental stability. The main methods for making polyaniline materials into film structures include electrochemical method, in-situ oxidative polymerization method, and spin coating method. The application of these methods is relatively mature and has its own advantages, but they all have certain limitations in specific applications. For example: although the thin films prepared by electrochemical methods have good conductivity and controllable thickness, they can only be formed on predetermined electrodes and cannot be transferred, and it is also difficult to achieve large-area preparation; the in-situ oxidative polymerization method requires the introduction of other dielectric layers between the substrate and polyaniline, which will affect the structure of the target device in practical applications; and the spin coating method requires the polymer powder obtained by the chemical oxidation method to be dissolved in an organic solvent and then spin-coated on the substrate to form a film. This method is not suitable for most organic substrates.
[0005] In addition, when using some existing methods to prepare polyaniline films, the controllability of the film thickness is generally low. If the conductive polymer film in the device is too thick, it will reduce the transmission of ions and detected objects, leading to problems such as long response time and high driving voltage. Increasing the pore structure of the polymer film and increasing the specific surface area of the film are effective methods to improve the response speed of conductive polymer electrical devices.
[0006] Therefore, it is extremely necessary to develop a method for preparing a large-area porous polyaniline film with controllable thickness on any substrate, which can provide the possibility for further expanding the application of polyaniline in different fields and provide new ideas for the preparation of conductive polymer organic electrochromic materials. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a method for preparing polyaniline film by self-assembly, which is simple to operate and has high preparation efficiency. A large-area regular and orderly pure polyaniline film can be prepared and transferred to any substrate.
[0008] In order to achieve the above technical purpose, the present invention is implemented by the following technical scheme: a method for preparing a polyaniline film by self-assembly, comprising the following steps:
[0009] 1) dissolving polyaniline powder in a solvent A miscible with water and ethanol to obtain a solution B, and mixing anhydrous ethanol with the solution B to obtain a solution C;
[0010] 2) adding the SDS aqueous solution dropwise into the deionized water in an open container to obtain solution D;
[0011] 3) After the drainage plate is hydrophilized, it is inserted obliquely into an open container so that the bottom of the drainage plate is immersed in solution D;
[0012] 4) Solution C is slowly dripped onto the drain plate from the top of the drain plate to form a uniform liquid film, and the solution flows downward into solution D, solvent A and ethanol are dissolved in water, and polyaniline is precipitated at the gas-liquid interface of solution D to self-assemble into a film;
[0013] 5) After standing for a period of time, the film is transferred to the target substrate and dried;
[0014] 6) The dried film is immersed in a dilute hydrochloric acid solution for doping, and dried to complete the preparation.
[0015] Furthermore, before step 6), ie, doping the film, steps 4) and 5) are repeated, so that polyaniline films of different thicknesses can be obtained by assembling layer by layer.
[0016] Furthermore, in step 5), after the single-layer film is transferred to the target substrate, it needs to be placed upright at an angle to evaporate the water on the surface of the film before subsequent operations are performed.
[0017] Furthermore, the concentration of polyaniline in the solution B prepared in step 1) is 7-10 mg / mL, and the volume ratio of anhydrous ethanol and solution B when mixed is 1:2-1:1.
[0018] Furthermore, in step 2), the concentration of the SDS aqueous solution used was 0.5 g / mL, and the interface SDS molecular concentration of solution D was 9.63×10 -6 mol cm -2 -1.44×10 -5 mol cm -2 .
[0019] Furthermore, in step 3), the drainage plate used is a polished glass sheet, a silicon sheet or other substrates with smooth surfaces, and the drainage plate is obliquely inserted into the open container at an inclination angle of 45°-60°.
[0020] Furthermore, the dripping speed of solution C added onto the drainage plate was 0.56-1.1 μL·cm -2 ·s -1 .
[0021] Furthermore, the substrate used in step 5) includes but is not limited to one of silicon wafer, glass, polydimethylsiloxane (PDMS), polyethylene terephthalate (PET), and the substrate needs to be hydrophilically treated by O2 plasma or UV-ozone method.
[0022] Furthermore, the concentration of the dilute hydrochloric acid used in step 6) is 1 mol·L -1 .
[0023] Furthermore, in step 6), the drying process is carried out in a vacuum drying oven at a drying temperature of 50° C.-70° C. and a drying time of 8-12 h.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present application uses the method of interfacial recrystallization to realize the self-assembly of polyaniline film. The prepared polyaniline film has an obvious three-dimensional network structure. By selecting the specifications of the guide plate, the large-area preparation of the polyaniline film can also be realized;
[0026] 2. The polyaniline film prepared by the method disclosed in this application can be transferred to any substrate, and since no other organic solvent is required to assist in the transfer process, it is suitable for the transfer of most organic substrates;
[0027] 3. The thickness of the single-layer polyaniline film prepared by the polyaniline film preparation method disclosed in the present application is between 9 and 20 nm. The thickness of the single-layer film can be adjusted by adjusting the polyaniline concentration. On this basis, the thickness of the film can be further controlled at the nanoscale by using a layer-by-layer assembly method, thereby realizing the controllable preparation of polyaniline films of different thicknesses;
[0028] 4. When the polyaniline film is prepared and substrate transferred using the method disclosed in the present application, no other medium needs to be introduced between the substrate and the polyaniline film, so that the performance and structure of the target device will not be affected in practical applications;
[0029] 5. The preparation method disclosed in the present application has a simple process and can be carried out under ambient conditions. It has low technical difficulty and strong operability, which is conducive to the large-scale promotion and use of the method and also provides a new idea for the preparation of this type of membrane material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a picture of a film formed by self-assembly of a polyaniline solution at the interface through recrystallization;
[0031] Figure 2 is a scanning electron microscope image of the polyaniline film obtained in Example 1;
[0032] Figure 3a are photographs of polyaniline films of different thicknesses obtained in Example 1 and Example 2;
[0033] Figure 3b are photos of polyaniline films obtained under different polyaniline concentrations, different solvents and varying SDS application amounts, wherein (a), (b) and (c) are photos of polyaniline films obtained in Examples 3, 4 and 5, respectively;
[0034] Figure 4 This is a photo of a large-area polyaniline film prepared on a flexible PET substrate;
[0035] Figure 5 This is a spectrum diagram showing the changes in the transmission spectrum of the electrochromic device assembled based on the polyaniline film prepared in Example 1 at different voltages. DETAILED DESCRIPTION
[0036] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0037] Main raw material sources:
[0038] Polyaniline (emerraldine base), Mw=50,000, was purchased from Sigma-Aldrich; dimethyl sulfoxide (ACS reagent, ≥99.9%) was purchased from Sigma-Aldrich; sodium dodecyl sulfate (SDS, ACS, ≥99.0%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0039] Example 1
[0040] 1) Dissolve 150 mg of commercial intrinsic polyaniline powder in 15 mL of dimethyl sulfoxide solution to obtain a concentration of 10 mg mL -1 15 mL of anhydrous ethanol was mixed with the polyaniline solution, and the mixture was stirred for 5 min for later use;
[0041] 2) Dissolve 50 g of sodium dodecyl sulfate (SDS) in 100 mL of deionized water to obtain a concentration of 0.5 g mL -1 SDS solution; add 500 mL of deionized water to a circular culture dish with a diameter of 20 cm, then take 0.5 mL of SDS solution and slowly add it dropwise to the deionized water in the culture dish, and let it stand for 1 minute;
[0042] 3) The polished glass (3 cm × 3 cm) used as the drain plate was hydrophilized using an O2 plasma cleaner and fixed to the edge of the culture dish. The drain plate was inserted into the culture dish at an angle of 60° so that the lower edge of the drain plate was immersed in the solution in the culture dish.
[0043] 4) The ethanol-polyaniline mixed solution prepared in 1) was diluted with water at 5 μL·s -1 The polyaniline solution forms a uniform liquid film on the drain plate. During the downward flow of the solution, dimethyl sulfoxide, ethanol and water are miscible, and the precipitated polyaniline molecules self-assemble into a film at the gas-liquid interface of the solution (see Appendix). Figure 1 );
[0044] 5) After standing for 1 minute, the film was transferred to a hydrophilic ITO glass sheet and placed upright at an angle (the angle between the film and the plane was between 45° and 60°) to allow the water on the film surface to evaporate naturally, and a single-layer film with a thickness of about 15 nm was obtained;
[0045] 6) repeating steps 4) and 5), transferring the assembled films one by one onto the film evaporated to dryness in step 5), assembling 20 layers in total, and obtaining a polyaniline film with a thickness of about 300 nm;
[0046] 7) placing the naturally dried film obtained in step 6) in a vacuum drying oven and baking at 70° C. for 5 h to completely dry the film;
[0047] 8) The dried polyaniline film was placed in a 1 mol·L -1 The film was immersed in a dilute hydrochloric acid solution for 1 min to make the polyaniline doped into a conductive state. The doped film was blown dry with N2 gas, placed in a vacuum drying oven, and baked at 70°C for 5 h to obtain the desired film material.
[0048] Figure 2This is a scanning electron microscope image of the polyaniline film obtained in this example. It can be seen from the image that the obtained film material has a three-dimensional network structure.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is only in step 6). In this embodiment, by controlling the number of assembled layers of the polyaniline film, cumulatively assembled polyaniline films of 4 layers, 7 layers, 12 layers, 25 layers, and 35 layers are obtained, and the corresponding film thicknesses are approximately 60nm, 100nm, 180nm, 350nm, and 500nm, respectively.
[0051] The photos of polyaniline films of different thicknesses prepared in Example 1 and Example 2 can be found in Figure 3a .
[0052] Example 3
[0053] 1) 80 mg of commercial intrinsic polyaniline powder was dissolved in 10 mL of dimethyl sulfoxide solution to obtain a concentration of 8 mg mL -1 10 mL of anhydrous ethanol was mixed with the polyaniline solution, stirred for 5 min, and set aside;
[0054] 2) Dissolve 50 g of sodium dodecyl sulfate (SDS) in 100 mL of deionized water to obtain a concentration of 0.5 g mL -1 SDS solution; add 500 mL of deionized water to a circular culture dish with a diameter of 20 cm, then take 0.5 mL of SDS solution and slowly add it dropwise to the deionized water in the culture dish, and let it stand for 1 minute;
[0055] 3) The polished glass (3 cm × 3 cm) used as the drain plate was hydrophilized using an O2 plasma cleaner and fixed to the edge of the culture dish. The drain plate was inserted into the culture dish at an angle of 60° so that the lower edge of the drain plate was immersed in the solution in the culture dish.
[0056] 4) The ethanol-polyaniline mixed solution prepared in step 1) was diluted with water at 5 μL·s -1 The polyaniline solution is slowly dripped onto the drainage plate at a rate of 1.5 %. The polyaniline solution forms a uniform liquid film on the drainage plate. During the downward flow of the solution, dimethyl sulfoxide, ethanol and water are miscible, and the precipitated polyaniline molecules self-assemble into a film at the gas-liquid interface of the solution.
[0057] 5) After standing for 1 minute, the film was transferred to a hydrophilic ITO glass sheet and placed upright at an angle (the angle between the film and the plane was between 45° and 60°), and the water on the film surface was allowed to evaporate naturally to obtain a single-layer film with a thickness of about 11 nm;
[0058] 6) Repeat steps 4) and 5), transfer the assembled film to the evaporated film in step 5), and assemble 20 layers cumulatively to obtain a polyaniline film with a thickness of about 220 nm (see attached). Figure 3b ).
[0059] 7) placing the naturally dried film obtained in step 6) in a vacuum drying oven and baking at 70° C. for 5 h to completely dry the film;
[0060] 8) The dried polyaniline film was placed in a 1 mol·L -1 The film was immersed in a dilute hydrochloric acid solution for 1 min for doping. The doped film was dried with N2 gas, placed in a vacuum drying oven, and baked at 70°C for 5 h to obtain the desired film material.
[0061] Example 4
[0062] 1) Dissolve 150 mg of commercial intrinsic polyaniline powder in 15 mL of N-methylpyrrolidone (NMP) solution to obtain a concentration of 10 mg mL -1 15 mL of anhydrous ethanol was mixed with the polyaniline solution, stirred for 5 min, and set aside;
[0063] 2) Dissolve 50 g of sodium dodecyl sulfate (SDS) in 100 mL of deionized water to obtain a concentration of 0.5 g mL -1 SDS solution; add 500 mL of deionized water to a circular culture dish with a diameter of 20 cm, then take 0.5 mL of SDS solution and slowly add it dropwise to the deionized water in the culture dish, and let it stand for 1 minute;
[0064] 3) The polished glass (3 cm × 3 cm) used as the drain plate was hydrophilized using an O2 plasma cleaner and fixed to the edge of the culture dish. The drain plate was inserted into the culture dish at an angle of 60° so that the lower edge of the drain plate was immersed in the solution in the culture dish.
[0065] 4) The ethanol-polyaniline mixed solution prepared in step 1) was diluted with water at 5 μL·s -1 The polyaniline solution is slowly dripped onto the drain plate at a rate of , and a uniform liquid film is formed on the drain plate. During the downward flow of the solution, NMP, ethanol and water are miscible, and the precipitated polyaniline molecules self-assemble into a film at the gas-liquid interface of the solution;
[0066] 5) After standing for 1 minute, the film was transferred to a hydrophilic ITO glass sheet and placed upright at an angle (the angle between the film and the plane was between 45° and 60°) to allow the surface water of the film to evaporate naturally, and a single-layer film with a thickness of about 15 nm was obtained;
[0067] 6) Repeat steps 4) and 5), and successively transfer the assembled films to the evaporated film in step 5), and assemble 20 layers cumulatively to obtain a polyaniline film with a thickness of about 300 nm (see attached). Figure 3b );
[0068] 7) placing the naturally dried film obtained in step 6) in a vacuum drying oven and baking at 70° C. for 12 h to completely dry the film;
[0069] 8) Place the dried polyaniline film in 1 mol·L -1 The film was immersed in a dilute hydrochloric acid solution for 1 min for doping. The doped film was dried with N2 gas, placed in a vacuum drying oven, and baked at 70°C for 5 h to obtain the desired film material.
[0070] It can be seen from the observation of the polyaniline film prepared in Example 3-4 that the thickness of the polyaniline film can be controlled by changing the concentration of polyaniline.
[0071] Example 5
[0072] The difference between this embodiment and embodiment 1 is only in step 2). The specific content of step 2) in embodiment 5 is: 50g sodium dodecyl sulfate (SDS) is dissolved in 100mL of deionized water to obtain a concentration of 0.5g mL -1 SDS solution; add 500 mL of deionized water to a circular culture dish with a diameter of 20 cm, then take 0.4 mL of SDS solution and slowly add it dropwise into the deionized water, and let it stand for 1 minute;
[0073] After 20 layers were assembled, a polyaniline film with a thickness of about 300 nm was obtained (see Appendix Figure 3b )
[0074] Example 6
[0075] The difference between this embodiment and embodiment 1 is only in step 5). The specific content of step 5) in embodiment 6 is: after the film is left to stand for 1 minute, the film is transferred to a hydrophilically treated flexible PET substrate, and placed upright at an angle (the angle between the film and the plane is between 45° and 60°), and the water on the film surface is naturally evaporated to obtain a polyaniline film bonded to the flexible substrate (see attached). Figure 4 ).
[0076] Related performance tests
[0077] The main reagents and equipment involved in the test process: The electrochemical workstation used in the electrochemical test process is produced by Shanghai Chenhua Instrument Co., Ltd., model CHI 760E; the electrolyte solution is 1M LiCl solution. The spectrometer used in the transmission spectrum test is Ocean Insight QEPRO-FL, with a wavelength range of 350nm-1100nm.
[0078] The electrochemical redox performance test and electrochromic performance test of the polyaniline film obtained in Example 1 were performed using an electrochemical and spectrometer system. The polyaniline-ITO glass obtained in Example 1 was used as the working electrode, the ITO glass was used as the counter electrode, and a 1M LiCl solution was used as the electrolyte to assemble an electrochromic device. The spectrometer and the electrochemical workstation were connected, and the test voltage range of the cyclic voltammetry curve was set to -1.8V-1.8V, and the scanning speed was 50mV·s -1 , and simultaneously tested the transmission spectra of the device at different voltages, and recorded the changes in the transmission spectra of the polyaniline film at different redox states. The electrochromic device assembled with the polyaniline film showed different light responses at 0V, 1V and -1.5V (see Appendix Figure 5 ).
[0079] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A method for preparing a polyaniline film by self-assembly, characterized in that: The steps include: 1) dissolving polyaniline powder in a solvent A miscible with water and ethanol to obtain a solution B, and mixing anhydrous ethanol with the solution B to obtain a solution C; 2) adding the SDS aqueous solution dropwise into the deionized water in an open container to obtain solution D; 3) After the drainage plate is hydrophilized, it is inserted obliquely into an open container so that the bottom of the drainage plate is immersed in solution D; 4) Solution C is slowly dripped onto the drain plate from the top of the drain plate to form a uniform liquid film, and the solution flows downward into solution D, solvent A and ethanol are dissolved in water, and polyaniline is precipitated at the gas-liquid interface of solution D to self-assemble into a film; 5) After standing for a period of time, the film is transferred to the target substrate and dried; 6) soaking the dried film in a dilute hydrochloric acid solution for doping, drying, and completing the preparation; The concentration of polyaniline in the solution B prepared in step 1) is 7-10 mg / mL, and the volume ratio of anhydrous ethanol and the solution B when mixed is 1:2-1:
1.
2. The method for preparing a polyaniline film by self-assembly according to claim 1, characterized in that: Before doping the film, steps 4) and 5) are repeated to obtain polyaniline films of different thicknesses through layer-by-layer assembly.
3. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: In step 5), after the single-layer film is transferred to the target substrate, it needs to be tilted and placed upright to evaporate the water on the surface of the film before subsequent operations.
4. The method for preparing a polyaniline film by self-assembly according to claim 1, characterized in that: In step 2), the concentration of the SDS aqueous solution used was 0.5 g / mL, and the interface SDS molecular concentration of solution D was 9.63×10 -6 mol cm -2 -1.44×10 -5 mol cm -2 .
5. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: In step 3), the drainage plate used is a polished glass sheet or a silicon sheet, and the drainage plate is obliquely inserted into the open container at an angle of 45°-60°.
6. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: The dripping speed of solution C added to the drainage plate was 0.56-1.1 μL·cm -2 ·s -1 .
7. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: The substrate used in step 5) is one of silicon wafer, glass, polydimethylsiloxane, and polyethylene terephthalate, and the substrate needs to be hydrophilized by O2 plasma or UV-ozone method.
8. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: The concentration of dilute hydrochloric acid used in step 6) is 1 mol·L -1 .
9. The method for preparing a polyaniline film by self-assembly as claimed in claim 1, characterized in that: In step 6), the drying process is completed in a vacuum drying oven at a drying temperature of 50° C.-70° C. and a drying time of 8-12 h.
Citation Information
Patent Citations
Film self-assembling preparation method and device thereof
CN104629066A